Drifting together or falling apart? : The empirics of regional economic growth in post-unification Germany - Roberta Colavecchio; Declan Curran; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2005)
The objective of this paper is to address the question of convergence across German districts in the first decade after German unification by drawing out and emphasising some stylised facts of regional per capita income dynamics. We achieve this by employing non-parametric techniques which focus on the evolution of the entire cross-sectional income distribution. In particular, we follow a distributional approach to convergence based on kernel density estimation and implement a number of tests to establish the statistical significance of our findings. This paper finds that the relative income distribution appears to be stratifying into a trimodal/bimodal distribution.
Keywords: C14; R12; R11; 330; regional economic growth; Germany; convergence clubs; density estimation; modality tests; Regionale Entwicklung; Entwicklungskonvergenz; Sozialprodukt; Schätzung; Deutschland; Neue Bundesländer